Rational inattention during an RCT - Bartosz Maćkowiak; Mirko Wiederholt (European Central Bank (ECB), 2025)
We introduce an information provision experiment into a standard dynamic rational inattention model. We derive analytical results about how the treatment effect varies with characteristics of the environment and the individual. We use these results to discuss findings in the empirical literature on information provision experiments that can be explained by rational inattention of survey respondents and what this interpretation implies about behavior outside the survey.
Keywords: D8; D9; E7; 330; rational inattention; information provision experiment; randomized control trial